Gastric lavage to reduce feed intolerance among vigorous neonates >34 weeks born through meconium stained liquor: A comparative study - Manoj Kumar Gupta; Dhirendra Prasad Yadav; Mohammad Ashfaque Ansari; Mukendra Sah (Asian Journal of Medical Sciences, 2023)
Background: Feed intolerance during early postnatal period is common in newborns with meconium-stained liquor (MSL). Prophylactic gastric lavage in neonates delivered with MSL and its recommendation by some pediatric textbooks, despite negligible scientific evidence and evidence-based recommendations.